2015
DOI: 10.1038/onc.2015.375
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of STK11 and TP53 with KRAS mutation-associated gene expression, proliferation and immune surveillance in lung adenocarcinoma

Abstract: While mutations in the KRAS oncogene are amongst the most prevalent in human cancer, there are few successful treatments to target these tumors. It is also likely that heterogeneity in KRAS-mutant tumor biology significantly contributes to the response to therapy. We hypothesized that presence of commonly co-occurring mutations in STK11 and TP53 tumor suppressors may represent a significant source of heterogeneity in KRAS-mutant tumors. To address this, we utilized a large cohort of resected tumors from 442 lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
253
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(260 citation statements)
references
References 46 publications
5
253
1
1
Order By: Relevance
“…Therefore, we performed NanoString assays for FFPE tumor-derived RNAs from 5 LKB1-WT and 5 LKB1-mutant human LUAD specimens. The LKB1 gene mutation status was analyzed by exon sequencing as previously described (19), and the results are shown in Supplemental Table 7. LINC00473 expression was consistently found to best correlate with tumor LKB1 status among all the genes tested ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we performed NanoString assays for FFPE tumor-derived RNAs from 5 LKB1-WT and 5 LKB1-mutant human LUAD specimens. The LKB1 gene mutation status was analyzed by exon sequencing as previously described (19), and the results are shown in Supplemental Table 7. LINC00473 expression was consistently found to best correlate with tumor LKB1 status among all the genes tested ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, LKB1 loss impaired the responses of KRAS mutant NSCLC to docetaxel monotherapy; the combination therapy of docetaxel and the MEK inhibitor selumetinib; or dual inhibition of the PI3K and MEK pathways (16,17). Additionally, LKB1 mutations were associated with the modulation of immune microenvironments, thus potentially impacting immunotherapeutic outcomes (18,19). The current data emphasize the need to determine tumor LKB1 status for patient stratification for evaluating therapeutic responses and identifying effective treatments.…”
Section: Introductionmentioning
confidence: 96%
“…Some researchers reported that concurrent STK11 and KRAS mutations did not affect the aggressiveness of the disease in patients [48,63]. Findings from other studies show that STK11 can potentiate tumor progression in KRAS-mutant tumors in mouse models [64] and was associated with a more aggressive disease [36]. It is possible that this discrepancy might be due to the presence of other alterations in subpopulations of KRAS mut /STK11 mut lung cancer.…”
Section: Cc-by-ndmentioning
confidence: 60%
“…STK11 also seems to have additional effects in KRAS-mutant tumors. Mutations in STK11 was shown to suppress the immune surveillance in KRAS-mutant lung cancer, and they might serve as a predictor of de novo resistance in immune checkpoint blockade [36,37]. In summary, I identified at least six genes downstream of RTK activation that were mutated in the PI3K/AKT/mTOR pathway.…”
Section: Mutation Of Genes Involved In the Mapk And Pi3k/akt/mtor Patmentioning
confidence: 99%
“…and dependent of the coexisting mutated KRAS. (52) Recently, Zhu et al suggested that multitargeted therapy is required to combat NSCLC. Combining a group of inhibitors in a novel fashion could provide better results.…”
Section: Disclosurementioning
confidence: 99%